Ventilator-Associated Pneumonia (VAP) Prevention Strategy by Increasing Nurse Compliance in the Implementation of VAP Bundles and the Implementation of Pulmonary Infection Score: A Systematic Review - Herawati, Netti; Muhith, Abdul; Zahroh, Chilyatiz (Journal of Applied Nursing and Health, 2024)
Background: Ventilator-associated pneumonia (VAP) is a nosocomial infection that occurs in patients receiving mechanical ventilation and is one of the main complications that can increase morbidity, mortality, and treatment costs in hospitals, especially in intensive care units (ICUs). The purpose of this study is to analyze the action of the VAP prevention strategy by increasing nurse compliance in the implementation of VAP bundles and the implementation of pulmonary infection score (CPIS) Methods: In this method of Systematic Review with Literature Search and Selection, systematic searches are carried out in Sage Journal, Science Direct, and PubMed databases. The search feature uses Boolean logic by utilizing the principles of AND, OR, and AND NOT. The keywords used include: "VAP," "CPIS," "VAP Bundle," and "HAIs." Of the included studies published from 2020 to 2024, peer-reviewed research in nursing and medical journals. Results: Overall, effective VAP prevention requires a holistic and integrated approach. Increasing nurse compliance in implementing the VAP Bundle and the implementation of CPIS in the early diagnosis of lung infections are two complementary strategies to prevent and manage VAP. Conclusion: To achieve optimal outcomes, hospitals and healthcare facilities must provide ongoing training, facilitate access to adequate resources, and improve communication and collaboration between medical teams.